Disrupting Colonial Trauma Through the Hyperconsumption of Outside Foods in India? A Digital Food Consumer Citizenship - Müller-Hansen, Merle (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
This article addresses the understudied intersection of digital food cultures, consumer citizenship, and colonial trauma within the context of India. While existing scholarship has examined food cultures in India and their colonial legacies, the role of internet-mediated practices in reconfiguring these dynamics remains understudied. This article bridges this gap by conceptualizing digital food consumer citizenship and analyzing how digital spaces mediate aspirational eating of outside foods as both a continuation of socio economic inequalities and a potential disruption of colonial trauma. To begin, the article examines the global history of Indian cuisine, exposing how colonial culinary politics shaped enduring inequalities and cultural hierarchies. Secondly, consumer citizenship debates open perspectives on participation in the era of economic liberalization and food cultures crossing class and urban-rural boundaries. Third, the analysis of digital food economies introduces the concept of smart food spaces to describe digital and sensor-driven transformations in food consumption settings, critiquing their role in hyperconsumption alongside their disruptive possibilities. The article moves on to explore aspirational eating in internet-mediated food cultures among India’s heterogenous urban middle classes, particularly younger generations, as an expression of participatory global food citizenship that challenges post-colonial classifications. By foregrounding subaltern agency and diverse innovative practices, such as adaptive digital platforms of local community kitchens, the article explores the potential of digital food cultures to de-center global power structures, disrupt colonial legacies, and create counter spaces that thrive otherwise. Finally, it proposes empirical research directions to further understand digital food consumer citizenship and its implications for food justice.